Financially Independent Based on Vegetable Self-Sufficiency Technology - Anwar, Syaiful; Hamzah, Zeze Zakaria; Subagyo, Wawan Hari; Wulandari, Devi; Safitri, Destalista Dewi; Oktaviana, Ananda (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Vegetable consumption in Indonesia is still low, reaching only 173 grams per day, far from the WHO recommendation of 400 grams. To address this problem, a community service program in RW 18 Karadenan, Bogor, applies hydroponic technology for housewives and single parent mothers. This program includes socialization and training on hydroponic techniques, including the Nutrient Film Technique (NFT) and Deep Flow Technique (DFT) systems, as well as the use of used containers. The training also includes organic vegetable marketing strategies and financial management using the full costing method to determine the cost of goods sold. Continuous mentoring and periodic evaluations are carried out to ensure the effectiveness of the technology and maximize harvest yields. This program aims to improve participants' farming skills, support family food security, and encourage economic independence. By implementing hydroponics, this program is expected to meet vegetable needs, increase family income and provide efficient farming solutions, and has the potential to be expanded to other areas.